ENVIRONMENTAL PROTECTION: पर्यावरण संरक्षण सब का दायित्व - Sharma, Purnendu (International Journal of Research -GRANTHAALAYAH, 2015)
From the beginning of the world to the present age, man has set a long journey of development. But in this journey, he has come forward alone leaving behind the eternal truth of life, as a result of which the catastrophic problems of the environment have taken birth and the world community has been trying to move forward by grappling with them for the past several decades. In view of its seriousness in 1972, a United Nations Conference was held in Stockholm, in which Mrs. Indira Gandhi, in her statement given for the protection of environment and welfare of mankind, said, "Man cannot be a civilized and true human being unless That he should not view the entire human civilization and the whole world in a friendly manner. In his statement, he highlighted the superiority of Vedic tradition and Indian way of life for environmental protection. सृष्टि के प्रारम्भ से वर्तमान युग तक मनुष्य ने विकास की लम्बी यात्रा तय की है। किन्तु इस यात्रा में वह जीवन के शाश्वत सत्य को पीछे छोड़कर अकेला आगे निकल आया है जिसके परिणाम में पर्यावरण की प्रलयंकारी समस्याओं ने जन्म ले लिया है और विश्व समुदाय विगत कई दशकों से इनसे जूझता हुआ आगे बढ़ने का प्रयास कर रहा है। 1972 में इसकी गम्भीरता को देखते हुए स्टाॅकहोम में संयुक्त राष्ट्र सम्मेलन आयोजित किया गया जिसमें श्रीमती इन्दिरा गांधी ने पर्यावरण संरक्षण एवं मानव जाति के कल्याण हेतु दिये गये अपने वक्तव्य में कहा कि, ’’मनुष्य तब तक सभ्य एवं सच्चा मानव नहीं हो सकता जब तक कि वह सम्पूर्ण मानव सभ्यता एवम् सम्पूर्ण सृष्टि को मित्रभाव से न देखे। अपने वक्तव्य में पर्यावरण संरक्षण हेतु वैदिक परम्परा एवम् भारतीय जीवन पद्धति की श्रेष्ठता को रेखांकित किया।